T2* "susceptibility vessel sign" demonstrates clot location and length in acute ischemic stroke. - Olivier Naggara; Jean Raymond; Montserrat Domingo Ayllon; Fawaz Al-Shareef; Emmanuel Touzé; Meriem Chenoufi; Sophie Gerber; Charles Mellerio; Matthieu Zuber; Jean Francois Meder; Jean-Louis Mas; Catherine Oppenheim (PLoS ONE, 2013)
OBJECTIVES:The aim of our study was to evaluate, in acute ischemic stroke patients, the diagnostic accuracy of the MRI susceptibility vessel sign (SVS) against catheter angiography (DSA) for the detection of the clot and its value in predicting clot location and length. MATERIALS AND METHODS:We identified consecutive patients (2006-2012) admitted to our center, where 1.5 T MRI is systematically implemented as first-line diagnostic work-up, with: (1) pre-treatment 6-mm-thick multislice 2D T2* sequence; (2) delay from MRI-to-DSA <3 hrs; (3) no fibrinolysis between MRI and DSA. The location and length of SVS on T2* was independently assessed by three readers, and compared per patient, per artery and per segment, to DSA findings, obtained by two different readers. Clot length measured on T2* and DSA were compared using intra-class correlation coefficient (ICC), Bland & Altman test and Passing & Bablok regression analysis. RESULTS:On DSA, a clot was present in 85 patients, in 126 of 1190 (10.6%) arteries and 175 of 1870 (9.4%) segments. Sensitivity of the SVS, as sensed by the used protocol at 1.5 T, was 81.1% (69 of 85 patients) and was higher in anterior (55 of 63, 87.3%), than in posterior circulation stroke (14 of 22, 63.6%, p=0.02). Sensitivity/specificity was 69.8/99.6% (per artery) and 76.6/99.7% (per segment). Positive (PPV) and negative predictive value (NPV) and accuracy were all >94%. Inter- and intra-observer ICC was excellent for clot length as measured on T2* (ĸ ≥ 0.97) and as measured on DSA (ĸ ≥ 0.94). Correlation between T2* and DSA for clot length was excellent (ICC: 0.88, 95%CI: 0.81-0.92; Bland & Altman: mean bias of 1.6% [95%CI: -4.7 to 7.8%], Passing & Bablok: 0.91). CONCLUSIONS:SVS is a specific marker of clot location in the anterior and posterior circulation. Clot length greater than 6 mm can be reliably measured on T2*.